2020
DOI: 10.1038/s41467-020-16670-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of air and surface contamination by SARS-CoV-2 in hospital rooms of infected patients

Abstract: Understanding the particle size distribution in the air and patterns of environmental contamination of SARS-CoV-2 is essential for infection prevention policies. Here we screen surface and air samples from hospital rooms of COVID-19 patients for SARS-CoV-2 RNA. Environmental sampling is conducted in three airborne infection isolation rooms (AIIRs) in the ICU and 27 AIIRs in the general ward. 245 surface samples are collected. 56.7% of rooms have at least one environmental surface contaminated. High touch surfa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
745
7
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 788 publications
(867 citation statements)
references
References 15 publications
51
745
7
21
Order By: Relevance
“…Evidences suggested that environmental contamination with SARS-CoV-2 is likely to be high, and it is supported by recent researches focus on environmental contamination from COVID-19 cases in hospital [5][6][7][8]. Hospitals already have perfect disinfection measures and are less likely to appear super-spreaders compared with community and family [4,[9][10][11].…”
Section: Introductionmentioning
confidence: 94%
“…Evidences suggested that environmental contamination with SARS-CoV-2 is likely to be high, and it is supported by recent researches focus on environmental contamination from COVID-19 cases in hospital [5][6][7][8]. Hospitals already have perfect disinfection measures and are less likely to appear super-spreaders compared with community and family [4,[9][10][11].…”
Section: Introductionmentioning
confidence: 94%
“…A recent study has described a low percentage of positive samples in an emergency room and the sub-intensive care ward (11). In another study, almost 57% of rooms treating COVID-19 patients had at least one environmental surface contaminated (12).…”
Section: Discussionmentioning
confidence: 94%
“…When using sing a human adenovirus virus (HAdV), Verani et al, 52 found 135 out of 172 surfaces within toilet facilities in a health care setting to be contaminated. Contamination of contact surfaces outside the sanitation setting has been reported in hospitals 55,56,57,58 home settings 59,60,61 and public spaces 60 .…”
Section: Discussionmentioning
confidence: 99%